P0111 Sub-ventricular zone irradiation in glioblastoma: Can it increase survival?. (July 2015) - Ravind, R.R.; Prameela, C.G.; Dinesh, M.
Abstract : Background: Glioblastoma multiforme are aggressive tumours with high relapse rates, which could be attributed to the neural progenitor stem cells in the sub-ventricular zone (SVZ). Irradiation of stem cell niche in the SVZ could translate into increased overall survival. We aimed to correlate the radiation dose received by the SVZ and its effect on overall survival. Methods: We did a retrospective analysis of data from patients with glioblastoma multiforme (treated at our institute in 2008–10) whose treatment plans could be retrieved and for whom current clinical status was known. All adult patients who underwent maximum safe resection and concurrent chemoradiation followed by adjuvant chemotherapy, were included in the study. The planning CT were de-archived, SVZ was contoured in axial segments by taking a 3 mm and 5 mm auto-margin lateral to the lateral ventricle. Laterality of the SVZ was determined according to the tumour epicentre and was denoted as ipsilateral SVZ (IL SVZ), contralateral SVZ (CL SVZ) and combined volume of SVZ (Comb SVZ). Irradiation doses received by each structure were analysed. Findings: 50 patients were included. The ratio of men to women was 66:34. Recursive partitioning analysis classified 28% of tumours as RPA class grade 3, 62% as grade 4, and 10% as grade 5. Gross total excision was done in 46%, sub-total resection was done in 54%. Median overall survival was 15.63 months (95% CI 8.83–22.43). Doses >50 Gy to IL SVZ (both 3 mm and 5 mm) were associated with a significant increase in overall survival (median OS 19.83 months versus 6.07 months; p = 0.031). Doses > 37 Gy to the CL SVZ (3 mm) were associated with a non-significant increase in overall survival (median OS 16.73 months versus 8.73 months; p = 0.305). Doses > 37 Gy to the CL SVZ (5 mm) were associated with a non-significant increase in overall survival (median 19.83 months versus 8.73 months; p = 0.118). Interpretation: Irradiation of potential cancer stem cell niches in the SVZ influences overall survival in glioblastoma multiforme. Increased doses to the IL SVZ are associated with increased survival in glioblastoma multiforme. Further studies are needed to know what dose should be delivered to what portion of the SVZ to attain this survival advantage. Age, KPS, RPA, extent of surgical resection, and various other biological factors also play an important part.